Confiança e desempenho organizacional: um estudo sobre a relação interorganizacional na prestação de serviço de festas infantis - Caselani, Denise Maria Candiotto (2009)
Based on the relational perspective reasoning this doctoral dissertation proposed a model that theorizes on the relationship between organizational and individual trust, cooperative behaviors and organizational performance in the sector of entertainment, specifically children parties businesses segment. An extensive literature review was conducted to better understand the definition of those variables and their theoretical relationship. The review also helped to identify scales used in previous research to measure the research variables. The identified scales were then back translated and adapted to be used in this research. The cooperative behavior scale was translated and tested in other studies conducted in Brazil and as the procedures used in those studies were reliable we used the scale from Hashiba (2008). The research instrument was pre-tested during the first part of the research in which deep interviews were conducted with manufacturers of equipment for entertaining children, like professionals toys used in parks and their customers. This phase of the study also helped to better understand the business segment and the relationship between the players in the business. In the next phase of the research the boundary spanner of each company in the business segment was contact and those that accepted to take part in the study was personally helped to fill the research questionnaire. Some 158 good responses were available in the end of data collection. The data was then analyzed using the statistical packages Stata and Amos. The last one allowed to test validation of the research constructs through SEM. Validation of the research constructs were reached and the basic model had a good fit. The results from both phases of the research show that organizational and individual trust are highly correlated but they are different constructs. Cooperative behaviors were explained by organizational trust and that only joint problem solve is the only cooperative behavior tested which explain organizational performance. The data also indicated that flexibility in the negotiation is negative related to performance. These findings corroborate previous researches in the field and also helped to further the knowledge on the subject.